The Influence of Price and Promotion on the Decision to Use Services at Rosebeauty Studio in Pasar Kemis Tangerang Banten - Cahyani, Herdina Dwi; Munarsih (IJESS International Journal of Education and Social Science, 2024)
The purpose of this study was to determine how Price and Promotion Influence the Decision to Use Services at Rosebeauty Studio in Pasar Kemis Tangerang both partially and simultaneously. The method used in this study is an associative method with a quantitative approach. The sampling technique used is the Slovin technique with a sample of 98 respondents. Data analysis using validity tests, reliability tests, classical assumption tests, descriptive analysis, simple regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study price has a positive effect on user decisions with the regression equation Y = 18.028 + 0.579 X1. The correlation value of 0.621 means that the two variables have a strong relationship with a determination coefficient of 38.6% while the remaining 61.4% is influenced by other factors. Hypothesis testing obtained t count> t table or (67.765> 1.985). Thus H0 is rejected and Ha is accepted, meaning there is a significant influence between price and decision to use services. Promotion has a positive effect on decision to use services with the regression equation Y = 8.293 + 0.774 X2, the correlation coefficient is 0.754, meaning that both variables have a strong relationship with a determination coefficient of 56.8% while the remaining 43.2% is influenced by other factors. Hypothesis testing obtained a calculated t value> t table or (11.242> 1.985). Thus H0 is rejected and Ha is accepted, meaning there is a significant influence between Promotion and decision to use services. Price and promotion have a positive effect on decision to use services with the regression equation Y = 6.931 + 0.185 X1 + 0.635 X2. The correlation coefficient value or level of relationship between the independent variable and the dependent variable is obtained at 0.768, meaning that it has a strong relationship with a simultaneous determination coefficient value of 58.9% while the remaining 41.1% is influenced by other factors. Hypothesis test obtained F count value > F table or (68.152 > 3.090). Thus H0 is rejected and Ha is accepted. This means that there is a significant simultaneous influence between price and promotion on the decision to use services at Rosebeauty Studio in Pasar Kemis Tangerang.